Analisis Pengaruh Belanja Pendidikan dan PDRB Per Kapita Terhadap IPM di Provinsi Jawa Timur - Intan Khairrun Nissa; Debby Nindya Istiandari (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2026)
This study aims to analyze the effect of education expenditure and Gross Regional Domestic Product (GRDP) per capita on the Human Development Index (HDI) of regencies/municipalities in East Java Province during the 2019–2023 period. The research applies a quantitative approach using secondary data obtained from the Central Bureau of Statistics (BPS), including education expenditure, GRDP per capita, and HDI. Data analysis was carried out using panel regression with the Random Effect Model. The results indicate that education expenditure has no significant effect on HDI, while GRDP per capita has a positive and significant effect on HDI. Simultaneously, both variables significantly influence HDI with an R-squared value of 0.984111, which means the model can explain 98.4% of the variation in HDI, while the remaining 1.6% is explained by other factors outside the model. These findings highlight that improvements in HDI in East Java are more strongly driven by economic growth, although the effectiveness of education expenditure remains crucial to be optimized to provide a tangible impact on human development quality.